The therapeutic potential of relaxin for heart failure with preserved ejection fraction. (3rd October 2022) - Salama, G; Palma, J; Gabris-Weber, B; MacMahon, B; Kuhn, B; Dschietzig, T; Romero, G
Abstract: Background and significance: Heart Failure (HF) is the leading cause of cardiovascular deaths and ∼50% of HF patients have HF with preserved ejection Fraction (HFpEF). HFpEF patients typically have co-morbidities such as atrial fibrillation (AF), diabetes, lung edema and hypertension. The latter is a predictor of mortality and is targeted to prolong survival given the lack of a direct therapy for HFpEF. To address this unmet public health problem, we investigate the therapeutic potential of the insulin-like hormone Relaxin (RLX) in a rat model of HFpEF that recapitulates most aspects of clinical HFpEF. Methods: ZSF1 diabetic rats were placed on a high fat diet (HFD for 11-weeks) and echocardiograms were used to track HFpEF development. At week 20, osmotic mini-pumps were implanted to release vehicle (Na-acetate) or RLX (400μg/kg/day, 2-weeks). Hearts were then perfused with a voltage-sensitive dye (RH237) and a Ca2+ indicator (Rhod-2/AM) to optically map action potentials and Ca2+ transients and analyze arrhythmia phenotype. Left ventricular (LV) tissue sections were used for immune-fluorescence (IF) imaging for changes in fibrosis (collagen 1), connexin 43, Wnt1 and β-catenin in LV myocytes. Blood draws were taken to measure changes in serum NT-pro-ANP, ET-1 and RLX. Results: ZSF1 rats on a HFD developed HFpEF with E/e' (an echo marker of diastolic dysfunction) decreasing to −24.4 from −17.9 MV (n=12) and was reversed to −18.6 MV by RLX (n=6, p<0.0001). In HFpEF rats that received the vehicle (n=6), a premature stimulus (S1-S2= 40 ms) elicited: a) no arrhythmia b) non-sustained AF or c) sustained AF, with (1/3 of rats in each group). RLX blocked sustained supraventricular (n=0/12) and n=4/12 had non-sustained AF. RLX improved conduction velocity (CV), at short cycle lengths (150 ms) from 0.74 to 0.9 m/s (n=4/group). IF indicated that RLX increased Cx43 (26.8±0.03%, p<0.0001, n=6), and β-catenin (52.8±0.05%, p<0.0001) at intercalated disks. RLX reduced collagen deposition in HFpEF rats (25±0.04%, p<0.04, back to normal) and caused a marked increase of cytosolic Wnt1 (47.3±0.06%, p<0.0001). IF data are given as mean ± SEM. Conclusions: The ZSF1 diabetic rat on a high-fat diet recapitulates most of the phenotypes associated with human HFpEF, including atrial arrhythmias, fibrosis, and lung edema. RLX treatment post-development of HFpEF reversed the pro-arrhythmic phenotype, increased conduction velocity particularly at fast heart rates, reversed fibrosis, reduced NT-pro-ANP and ET-1 in male rats. Most intriguing, RLX treatment activated Wnt1 and β-catenin indicating that the beneficial actions of RLX occur via genomic remodeling of the heart. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Relaxera Pharmazeutische Gesellschaft mbH & Co. KGStubenwald-Allee 8a, 64625 Bensheim, Germany & Uhlandstraße 4-5, 10623 Berlin, Germany